ASSESSMENT OF THE GROUNDWATER POTENTIAL AND QUALITY IN BHATSA AND KALU RIVER BASINS OF THANE DISTRICT, WESTERN DECCAN VOLCANIC PROVINCE OF INDIA - Shankar M.N.R.; Mohan G. (My University, 2006)
Scarcity of groundwater necessitates the present study to evaluate groundwater potential and quality for designing suitable water management plans in the Bhatsa and Kalu river basins in the Thane district in the western Deccan volcanic province of India. A Geographical Information System platform is used to integrate and spatially analyse multiparametric data comprised of satellite, topographical, geological and hydrogeological information to generate several thematic maps, including groundwater potential zonation map. This study reveals that 70% of the area has medium to low groundwater potential, while only 10% has high potential. The static and dynamic groundwater potentials are estimated to be 10.7 and 4.8% of the annual rainfall. The groundwater quality in terms of hardness, total dissolved solids, salinity and chloride is suitable for domestic and irrigational purposes. A database is developed for sustainable water management program for the region and areas where suitable water conservation techniques need to be adopted are identified.
Keywords: GIS; GROUNDWATER; GWPZ; QUALITY; INDIA